More freedom – more investments. The relationship between the extent of fiscal autonomy with respect to own revenues and investment expenditures of Polish communes and cities with county rights - Sekuła, Alicja; Basińska, Beata (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2016)
The purpose of this study was to investigate the relationship between own revenues characterized by different levels of fiscal autonomy and investment expenditures of selected local government entities in Poland. Accordingly, the following research hypothesis was formulated: there is a relationship between the type of own revenue identified with respect to fiscal autonomy and the size of investment expenditures. Revenues characterized by low or no fiscal autonomy are more likely to be earmarked for current expenditures. The study encompasses the 2003–2011 period. Two groups of local government entities were analyzed: cities with county rights and communes (with the exception of city communes that are cities with county rights, constituting the first group). The calculations carried out demonstrated that in both analyzed groups the revenues characterized by extensive fiscal autonomy (EFA), such as revenues from the property tax, had the greatest impact on investment expenditure: in communes, an increase in revenue in this group by PLN 1,000,000 resulted in an increase in investment expenditure by PLN 2,180,000, while in cities with county rights it increased by PLN 1,320,000. The general conclusion is that local government entities should be granted the type of own revenues that they are allowed to structure to the greatest extent, since this is the type of revenues that most fully translates into investment activity, thus ensuring the strongest stimulus for development
Argument Oeconomica, 2016, Nr 1 (36), s. 241-260
Keywords: own revenues; fiscal autonomy; investment expenditures; cities with county rights